ANALISA PERENCANAAN ENERGI TERBARUKAN SISTEM ATAP SURYA - Karseno April; Masbah R.T Siregar (Institut Sains dan Teknologi Nasional, 2021)
Planning for renewable energy for solar roof systems on house types 36,50 and 70 with the on-grid rooftop solar system design. Solar roofs are more aesthetically appealing and sleeker, the appearance of the roof is amazing which has a choice between textured tiles that blend into the building and can provide many advantages. Using the theory of calculating the area of the roof in the form of a prism, it can be seen the optimization of the area of the solar roof. The calculation results obtained, the larger the type of house and the length of the potential solar roof and the width of the potential solar roof, the more extensive the optimization of the solar roof area, the larger the type of house and the number of solar roof tiles required, the heavier the dimensions of the weight of the solar roof, the electric power. generated by the solar roof has the potential to save electricity to PLN, the economic investment of the solar roof that needs to be prepared with the calculation results for type 36 houses valued at Rp.194,504,000, type 50 Rp. 268,321,000 and type 70 Rp. 335,296,000.